1967
DOI: 10.1063/1.1712242
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Spectra and Space Group of Crystalline Hydrazine and Hydrazine-d4

Abstract: The infrared spectra of crystalline hydrazine and hydrazine-d4 have been recorded from 33 to 400 cm−1. All spectral bands have been assigned to lattice vibrations according to whether they arose primarily from a translational motion or a librational mode. However, there is strong evidence that these two motions are coupled and thus may not be described accurately as one motion or the other. An attempt is made at correlation between the observed and calculated shifts upon deuteration and some simple force const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…However, there is some doubt as to the crystal structure of solid hydrazine at atmospheric pressure. Baglin et al (1967) analyzed the optical modes of the crystal lattice in the far-IR region and pointed out that the crystal symmetry should be the P2 1 space group. Busing et al (1961) reported that the symmetry is P2 1 with two N 2 H 4 molecules per unit cell.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some doubt as to the crystal structure of solid hydrazine at atmospheric pressure. Baglin et al (1967) analyzed the optical modes of the crystal lattice in the far-IR region and pointed out that the crystal symmetry should be the P2 1 space group. Busing et al (1961) reported that the symmetry is P2 1 with two N 2 H 4 molecules per unit cell.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to potentiometry in cells B and C is to determine £i/2(K+) by polarographic techniques. 1 In principle, £i/2(K+) can often be equated with £°(K+), but the polarographic method requires that the system be reversible and that there be a relatively high concentration of some supporting electrolyte with the potassium salt. This introduces complications arising from ion association and salt effects, so that the potentiometric method in cell B or C is preferred.…”
mentioning
confidence: 99%
“…The molecule is planar, with a maximum deviation of 0.042 (1) Å for atom N3, and it has a trans configuration. The N2-N2 i bond distance [symmetry code: (i) 2 À x, Ày, 1 À z] corresponds to a single bond and is shorter than the corresponding distances found in hydrazine (1.46 Å ; Baglin et al, 1967) and in a related picolinamide azine [1.424 (3) Å ; Xu et al, 1997]. The N2-C1 bond is considered to have full double-bond character.…”
Section: Commentmentioning
confidence: 99%